2001
DOI: 10.1007/pl00000926
|View full text |Cite
|
Sign up to set email alerts
|

On the distribution of phytoecdysteroids in plants

Abstract: The occurrence and levels of phytoecdysteroids in the seeds and other parts of plants grown from the seeds of 180 randomly selected plant species were assessed and compared. Ecdysteroids are frequently detectable in leaves and flowers, but less so in stems, roots and seeds. The seeds of 290 species were assessed for the presence of hydrolysable ecdysteroid conjugates. Low levels of conjugates were detected in a significant number of species, large amounts being present only when levels of free ecdysteroids wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 22 publications
0
61
0
5
Order By: Relevance
“…Phytoecdysteroids are structurally related to the main insect hormone ecdysone. Plant species synthesize ecdysteroids with diverse structural variations [3].…”
mentioning
confidence: 99%
“…Phytoecdysteroids are structurally related to the main insect hormone ecdysone. Plant species synthesize ecdysteroids with diverse structural variations [3].…”
mentioning
confidence: 99%
“…A huge number of further ecdysteroids *Address correspondence to this author at the Department of Pharmacognosy, University of Szeged, H-6720 Szeged, Eötvös utca 6, Hungary; Tel: +3662/546-456; Fax: +3662/545-704; E-mail: Bathori@pharma.szote.u-szeged.hu have been isolated from various animal sources. It has been suggested that other ecdysteroids may play active roles in insects at different stages of their development [7].…”
Section: Introduction the Occurrence Of Ecdysteroids And Their Effectmentioning
confidence: 99%
“…1), found in plants such as Rhaponticum carthamoides, Serratula coronata, and Spinacia oleracea [6]. The prospect of studying the mechanism of action of 20 E is due to the lack of toxicity, and a manifestation of the tonic, anabolic, stress protective, gastroprotective, antihypoxic, and adaptogenic effects [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%